(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
An experiment was conducted to determine the effects of different levels of energy on growth performance of crossbred (Indigenous × Holstein Friesian) bull calves. Feeding trial was conducted for sixty days long with twelve numbers of crossbred bull calves having almost similar body weight (115±5 kg) and age (1 year and 9 months). The parameters of energy requirements for crossbred bull calves were feed intake (DM), nutrient intake, changes in body weight, daily live weight changes, feed conversion efficiency, co-efficient of digestibility of different nutrients, nutritive value and requirements of energy for maintenance and growth. Four levels of dietary energy (T0, T1, T2 and T3) were supplied to the experimental animals for this purpose. The level of ME was T0 = 17.4 MJ/d as maintenance ration, T1 = 20.22 MJ/d for 200 g/d targeted LWG, T2 = 23.37 MJ/d for 400 g/d targeted LWG, T3 = 27.29 MJ/d for 600 g/d targeted LWG. It was found that the average daily live weight gain in T1 (290 g) fulfills against the targeted live weight gain (200 g/d). On the other hand, the expected live weight gain for T2 and T3 (400 g/ d and 600 g/d) were not fulfill at the end of experiment. The energy requirement for 100 kg body weight of crossbred bull calves was 17.4 MJ d-1 as maintenance and 15.44 MJ d-1 required for growth of 200g/ d. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 246-254